Pengaruh Brand Coolness terhadap Willingness To Pay Dengan Emotional Brand Attachment sebagai Variabel Mediasi: Studi pada Gen Z Pengguna iPhone di Semarang - Theresia Putri Kharina Tarigan; Yoestini Yoestini (Diponegoro Journal of Management, 2025)
In the digital era, brand coolness plays a crucial role in shaping brand perception and purchasing decisions, particularly among Generation Z. iPhone has established a strong brand coolness image, reflecting not only technological innovation but also social status and self-expression. However, limited research has examined its impact on willingness to pay (WTP), particularly with emotional brand attachment as a mediating variable. This study aims to analyze the influence of brand coolness on WTP, with emotional brand attachment as a mediator, among Generation Z iPhone users in Semarang.Using a quantitative approach, data were collected from 200 respondents via an online survey and analyzed with Structural Equation Modeling (SEM) using AMOS.Results indicate that brand coolness positively influences emotional brand attachment, which in turn significantly affects willingness to pay. Additionally, brand coolness has a direct and indirect effect on WTP, with emotional brand attachment acting as a partial mediator. These findings highlight the importance of enhancing brand coolness to strengthen emotional connections and premium pricing justification among Generation Z consumers.